Cyclam-based iron(iii) and copper(ii) complexes: synthesis, characterization and application as antifungal agents. (16th August 2022) - Almada, Stephanie; Maia, Luísa B.; Waerenborgh, João C.; Vieira, Bruno J. C.; Mira, Nuno P.; R. Silva, Elisabete; Cerqueira, Fátima; Pinto, Eugénia; Alves, Luis G.
Abstract : Cyclam-based complexes of formulae [{H2 ( 4-CF3 PhCH2 )2 Cyclam}FeCl2 ]Cl and [{H2 ( 4-CF3 PhCH2 )2 Cyclam}Cu](CH3 COO)2 ·2H2 O reveal antifungal activity against diverse unicellular and multicellular fungal species. Abstract : New cyclam-based complexes of formulae [{H2 ( 4-CF3 PhCH2 )2 Cyclam}FeCl2 ]Cl and [{H2 ( 4-CF3 PhCH2 )2 Cyclam}Cu](CH3 COO)2 ·2H2 O were synthesized, in very high yields, by the reaction of H2 ( 4-CF3 PhCH2 )2 Cyclam with the corresponding metal salts in methanol. [{H2 ( 4-CF3 PhCH2 )2 Cyclam}FeCl2 ]Cl was also prepared, quantitatively, in the solid state by mechanochemistry. The Mössbauer spectra of [{H2 ( 4-CF3 PhCH2 )2 Cyclam}FeCl2 ]Cl show that the high-spin cis complex is the major product of both reactions. The EPR data of [{H2 ( 4-CF3 PhCH2 )2 Cyclam}Cu](CH3 COO)2 ·2H2 O are consistent with two distinct Cu 2+ species, whose solid state molecular structures were determined by single crystal X-ray diffraction and correspond to complexes displaying octahedral and square–pyramidal geometries. The screening of the antifungal activity of both metal complexes revealed the higher activity of [{H2 ( 4-CF3 PhCH2 )2 Cyclam}FeCl2 ]Cl to inhibit the growth of unicellular and multicellular fungal species with described pathogenic potential.